1993
DOI: 10.1177/030089169307900506
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of Thyroid Carcinomas: Reproducibility of the «Who» Classification

Abstract: Central pathology review of thyroid carcinomas is recommended when clinical and epidemiologic trials are planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…Furthermore, reliable prognostic markers are still insufficient. The most prominent interobserver variability has been reported in follicular-patterned tumors [175][176][177][178]. Final agreement for reported criteria such as capsular or vascular invasion and differential diagnosis of follicular adenoma and carcinoma is very low (27,20 and 37%, respectively) [177].…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reliable prognostic markers are still insufficient. The most prominent interobserver variability has been reported in follicular-patterned tumors [175][176][177][178]. Final agreement for reported criteria such as capsular or vascular invasion and differential diagnosis of follicular adenoma and carcinoma is very low (27,20 and 37%, respectively) [177].…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…Final agreement for reported criteria such as capsular or vascular invasion and differential diagnosis of follicular adenoma and carcinoma is very low (27,20 and 37%, respectively) [177]. Some disagreements between pathologists have also been reported for classification of histological variants of PTC and FNAB [175][176][177][178].…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…2 A review of 200 thyroid tumors by seven Italian pathologists revealed good agreement for papillary and anaplastic thyroid carcinomas, moderate for medullary and poor for follicular thyroid carcinomas. 3 In another review of 41 follicular carcinomas by five experienced French thyroid pathologists, the agreement for malignancy varied from 5% among all five pathologists to 56% between two pathologists. 4 Of concern, the interobserver and intraobserver agreements for vascular invasion were only 20 and 68%, respectively.…”
mentioning
confidence: 97%
“…The reproducibility of histological classification in thyroid carcinoma has previously been addressed in a few studies (Saxen et al, 1978;Holm et al, 1980;Fassina et al, 1993;Franc et al, 1999;Hirokawa et al, 2002). In most of these studies, the review of the cases was performed separately by each observer.…”
Section: Discussionmentioning
confidence: 99%
“…However, as in Fassina's study on cancer subclassification (Fassina et al, 1993), several debates occurred during our consensus conference when we were reviewing PTC subtypes and encapsulated thyroid follicular tumours. The level of agreement differed depending on It is important to note the increased diagnosis of papillary carcinoma follicular variant in the last decade, in adult, childhood and adolescent thyroid cancer (Harach and Williams, 1995;Pacini et al, 1997;Tronko et al, 1999;Verkooijen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%